Adaptability to Settlement Pattern and Choice of Subsistence Activities : Emergence of Material Culture within the Saribas Malay in Betong, Sarawak - Faridah, Sahari; Shahren, Ahmad Zaidi Adruce; Rahah, Hasan; Anna, Durin; Shahri, Abdul Rahman (EDP Sciences, 2018)
Despite many job opportunities in the market and the challenges they have to face, some minority of the Saribas Malay community in Betong, Sarawak is still maintaining traditional subsistence activities in food production based on the nipah tree (locally known as apong) such as gula apong, garam apong cuka apong, jarik mayang, air sadap and the sago tree (locally known as mulong) produce, lemantak. This research examines the choice of subsistence strategies and settlement pattern of the Malay community who inhabit the Saribas region. Through the in-depth interview and participant observation, the finding suggested that reliance on a river as the main highway to connect them to the other parts of Sarawak and river as a source of marine resources determine the choice of linear settlement pattern along the river. The results also suggest that river terrestrial resources; apong and mulong accessibility and abundance availability that influence the community in continuing the traditional subsistence activities (apong and mulong based food production) related to those flora source. As such, the assemblage of material culture that exist within the Saribas Malay community is the representation and manifestation of their choice of settlement pattern and subsistence activities.